2016
DOI: 10.1212/wnl.0000000000003361
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of psychogenic pseudosyncope

Abstract: Objective: To determine the outcome of patients with psychogenic pseudosyncope (PPS) after communication of the diagnosis.Methods: This was a retrospective cohort study of patients with PPS referred in 2007 to 2015 to a tertiary referral center for syncope. We reviewed patient records and studied attack frequency, factors affecting attack frequency, health care use, and quality of life using a questionnaire. We explored influences on attack freedom and attack frequency in the 6 months before follow-up for age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Indeed, half of our patients with the final diagnosis of PPS had also an established (three cases) or likely (four cases) diagnosis of VVS. This finding is consistent with the study by Saal et al . where the authors found that 57% of patients with the final diagnosis of PPS also had the diagnosis of syncope.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, half of our patients with the final diagnosis of PPS had also an established (three cases) or likely (four cases) diagnosis of VVS. This finding is consistent with the study by Saal et al . where the authors found that 57% of patients with the final diagnosis of PPS also had the diagnosis of syncope.…”
Section: Discussionsupporting
confidence: 93%
“…RAS attacks in young children cause fear and anxiety for both the patient and the caregiver (s), and future studies should aim to address this key knowledge gap. While our review was focused on the impact of orthostatic syncope and pre-syncope on quality of life, we recognize that other etiologies of syncope (e.g., cardiac syncope, psychogenic pseudosyncope) also have a negative impact on quality of life ( 21 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of the diagnosis by patients may be critical for therapy. In one observational study, 405 communicating and explaining the diagnosis resulted in an immediate reduction of attack frequency, with 39% of patients being asymptomatic during a mean follow-up period of 4 years. Some advice on how to inform the patient is provided in Web Practical Instructions section 10: European Society of Cardiology information sheet for patients affected by psychogenic pseudosyncope.…”
Section: Documentation Of Key Features During An Attackmentioning
confidence: 99%